Managing expectations : a memoir in essays - Driver, Minnie (HarperOne, an imprint of HarperCollinsPublishers, 2022)
"A charming, poignant, unfiltered, laugh-out-loud memoir in essays from beloved actor and natural-born storyteller Minnie Driver, chronicling the way life works out even when it doesn't"--